Assesing Users Preferences and their impact to public transport businessin Jakarta using Analytical Hierarchy Process (AHP) - Wijoseno, Hario; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2015)
Abstract.The Economic growth in Indonesia in line with the increase in the purchasing power of private vehicles will be to make ends meet. With the increasing number of vehicles being offset by the addition of the road, it creates bottlenecks that become an everyday sight in Jakarta. Transportation problem is exacerbated by the poor quality of the existing public transport, so that people prefer to use private vehicles.This study tried to find out what people's expectations for good public transportation in Jakarta and clicking the correlation with existing current transportation today there are Angkot, Regular Buss, Trans Jakarta and Commuter line. The method used in this study is Analytical Hierarchy Process, which do pairwaise of criteria-criteria appear. This thesis study using literature study mode, interviews with stakeholders and experts in transport, distribution of the questionnaire, data processing soft ware Expert Choice, the calculation of the score, and analysis. So that in can be an assessment of the four common trasnportasi Jakarta.The results of this study is AHP model that can utilize in determining and suggesting for policy maker and entrepreneurs on its Industry. From the Ahp we get the priority from the passanger choosing public transport is safety( 27,4%), followed by price 22,1%) and reliability 16,5%. By the improvement in term of comfort, safety, timeliness, environmental friendliness and adjusted price, expected to encouraging people for moving to public transport from private vehicle.KeyWord : Transportation, AHP, AHP model, AHP criteriaÂ